Effects of long-term athletic training on muscle morphology and tendon stiffness in preadolescence: association with jump performance - Pentidis, N.; Mersmann, F.; Bohm, S.; Giannakou, E.; Aggelousis, N.; Arampatzis, A. (European Journal of Applied Physiology, 2020)
Purpose: Evidence on training-induced muscle hypertrophy during preadolescence is limited and inconsistent. Possible associations of muscle strength and tendon stiffness with jumping performance are also not investigated. We investigated the thickness and pennation angle of the gastrocnemius medialis muscle (GM), as indicators for potential muscle hypertrophy in preadolescent athletes. Further, we examined the association of triceps surae muscle-tendon properties with jumping performance. Methods: Eleven untrained children (9 years) and 21 similar-aged artistic gymnastic athletes participated in the study. Muscle thickness and pennation angle of the GM were measured at rest and muscle strength of the plantar flexors and Achilles tendon stiffness during maximum isometric contractions. Jumping height in squat (SJ) and countermovement jumps (CMJ) was examined using a force plate. We evaluated the influence of normalised muscle strength and tendon stiffness on jumping performance with a linear regression model. Results: Muscle thickness and pennation angle did not differ significantly between athletes and non-athletes. In athletes, muscle strength was greater by 25% and jumping heights by 36% (SJ) and 43% (CMJ), but Achilles tendon stiffness did not differ between the two groups. The significant predictor for both jump heights was tendon stiffness in athletes and normalised muscle strength for the CMJ height in non-athletes. Conclusion: Long-term artistic gymnastics training during preadolescence seems to be associated with increased muscle strength and jumping performance but not with training-induced muscle hypertrophy or altered tendon stiffness in the plantar flexors. Athletes benefit more from tendon stiffness and non-athletes more from muscle strength for increased jumping performance.